Analisis Kasus Manipulasi Laporan Keuangan dan Penyelesaian Audit: Studi Kasus PT Garuda Indonesia - Ahmad Akil; Fina Ruzika Zaimar; Melanie Tumanan; Muh. Nurfaiz Alfarisi (STKIP Subang, 2025)
This study analyzes the financial statement manipulation case of PT Garuda Indonesia in 2018 and the audit process that followed. The study aims to explain how the manipulation occurred, how the audit addressed the case, and what factors influenced the auditor’s independence. The research uses a qualitative method with a case study approach based on public documents, audit reports, and regulatory sanctions. The findings show that Garuda Indonesia recognized revenue from a cooperation agreement with PT Mahata Aero Teknologi before meeting the criteria in PSAK. This recognition changed a large loss into a reported profit. Regulators required a restatement that confirmed a significant loss. The audit process found limited evidence on material accounts and high uncertainty about going concern, which led to a disclaimer opinion in 2020. The case shows that weak internal control, pressure on management, and poor governance increased fraud risk. The sanctions from OJK and the Ministry of Finance forced improvements in audit quality and governance. The study recommends stronger internal control, strict revenue recognition standards, and better independence for auditors to prevent similar cases.